Micro-terminator: 'Hasta la vista, lncRNA!' - Diederichs, Sven (Nature structural & molecular biology, 2015)
Transcriptional termination is an important yet incompletely understood aspect of gene expression. Proudfoot, Jopling and colleagues now identify a new Microprocessor-mediated mechanism of transcriptional termination, which acts specifically on long noncoding transcripts that serve as microRNA precursors.